(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Thyroid cancer is a relatively uncommon malignancy globally, with an estimated incidence ranging from 0.5 to 10 cases per 100,000 individuals. It accounts for a small proportion of all cancers, with approximately 0.5% in men and 1.5% in women. Objectives: This study aims to investigate the incidence and clinical characteristics of thyroid nodules and carcinoma in a Pakistani population. Study Design: A cross-sectional study Place and duration of study. A cross-sectional study was conducted at Watim medical and dental college, Rawat from 05 Jan 2019 to 05 July 2019 Materials and Methods: Ethical approval was obtained from the hospital's ethical committee. Data were obtained from 100 participants of both genders. Demographic data, clinical tables and tissue specimens were described. The patients went through Ultrasonography and Fine Needle Aspiration Cytology for the nodules that were clinically suspicious or were noticed on ultrasound. Results: The study included 100 patients, with a gender ratio of 7. 5:2. 5, female to male. The most common presentation of the patient was a swelling on the neck that moved with swallowing. Among patients, 78% had benign thyroid gland swellings and 22% had malignant tumours. Papillary carcinoma was the most prevalent malignant tumour, which had 22% of cases. Statistical analysis through the SPSS 20. 0 software showed that demographic and clinical factors such as age, gender, education, and profession were significantly associated with the presence of malignant tumours (p < 0. 05). These results highlight the significance of complete assessment and the presence of malignancy among patients with thyroid nodules, especially among those in countries with a high prevalence of thyroid cancer like Pakistan. Conclusion: The study points out a remarkable incidence of thyroid nodules and carcinoma in Pakistani society where papillary carcinoma is the most prevalent malignant tumour. This is especially true in a multinodular goitre, where 22% of cases have malignancy. Therefore, a detailed assessment is vital. This study confirms the need for early detection and a complete evaluation of thyroid nodules and carcinoma to have appropriate management.